KRITIK KUNTOWIJOYO TERHADAP ISLAMISASI ILMU - Fathony, Bimba Valid (UIN Sunan Kalijaga Yogyakarta, 2024)
As a form of response to the development of existing scientific paradigms, it is not uncommon for criticism to arise between each other. The development of the Islamization of science itself has given rise to criticism that the Islamization of science is only used as an instrument for the sterilization of modern science which is currently developing. So it has not yet emerged the true substance of Islam. In this research, researchers used qualitative research methods. This research is a type of library research, namely research whose object of study uses library data in the form of books, journals and articles as data sources. The results of the research entitled